The legal system for protecting local products in the federal state. A study in Iraqi and Kurdistan legislation - MareiShalgami, Amr Sayed (Journal of Legal and Political Studies)
The subject of this study is to establish a sound legal framework to protect local products in the federal system, using the Iraqi and Kurdistan legislation. We have come up with a review of the practices harmful to local products, and the administrative confrontation of those harmful practices stipulated in the Iraqi and Kurdistan legislation. We concluded that there is complementarity between the two aforementioned legislations with regard to that confrontation, and the extent of full coordination and cooperation between the federal authority and the Kurdistan Region to confront those practices based on the principle of reciprocity, and we also concluded that objective liability is the appropriate legal nature for civil liability arising from practices harmful to local products, Also, the idea of a mistake or harmful act of gain can be applied in the context of damage to local products, which leads to adopting the compensation estimate based on the severity of both the mistake and the damage, in contravention of the general rules. We reviewed the appropriate penalties for the gainful mistake that leads to harm to national products and local producers or competitors, apart from those penalties prescribed under the general rules. We concluded our study by talking about the extent of preference for local products in contracts concluded by the state or region with others. Keywords: National products - harmful practices - local producer - competing producer
Keywords: National products harmful practices local producer competing producer